Artists in the University Positioning Artistic Research in Higher Education - Wilson, Jenny (Springer Singapore, 2018)
This book focuses on the relationship between the university and a particular cohort of academic staff: those in visual and performing arts disciplines who joined the university sector in the 1990s. It explores how artistic researchers have been accommodated in the Australian university management framework and the impact that this has had on their careers, identities, approaches to their practice and the final works that they produce. The book provides the first analysis of this topic across the artistic disciplinary domain in Australia and updates the findings of Australia's only comprehensive study of the position of research in the creative arts within the government funding policy setting reported in 1998 (The Strand Report). Using lived examples and a forensic approach to the research policy challenges, it shows that while limited progress has been made in the acceptance of artistic research as legitimate research, significant structural, cultural and practical challenges continue to undermine relationships between universities and their artistic staff and affect the nature and quality of artistic work.